2020
DOI: 10.1080/23802359.2020.1829138
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Plagiodera versicolora (Laicharting)(Coleoptera: Chrysomelidae)

Abstract: Plagiodera versicolora (Laicharting) is a leaf-eating pest widely distributed in the world. In this study, the first complete mitochondrial genome of P. Versicolora (Laicharting) was assembled and analyzed. The complete mitochondrial genome of P. Versicolora (Laicharting) is 16,857 bp with 22.39% GC containing, 13 protein-coding genes, 22 transfer RNA (tRNA), 2 ribosomal RNA (rRNA), as well as an AT-rich region. Phylogenomic analysis indicated that P. Versicolora (Laicharting) is sister to Chrysomela populiThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies have shown that lignin and tannins are more effective against specialists, but alkaloids or flavonoids are considered primarily effective against generalists, indicating that condensed tannins are not the only indicator for poplar resistance to pests (Wang et al, 2012). P. versicolora is considered a generalist because it feeds on many plant species, such as poplar, willow, mulberry, maize and soybean (Thiel et al, 2020; Xie et al, 2020). Recent studies have found that flavonoids and anthocyanins are key secondary metabolites involved in plant responses to abiotic and biotic stresses (Ahmed et al, 2021; Wang, Li, et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that lignin and tannins are more effective against specialists, but alkaloids or flavonoids are considered primarily effective against generalists, indicating that condensed tannins are not the only indicator for poplar resistance to pests (Wang et al, 2012). P. versicolora is considered a generalist because it feeds on many plant species, such as poplar, willow, mulberry, maize and soybean (Thiel et al, 2020; Xie et al, 2020). Recent studies have found that flavonoids and anthocyanins are key secondary metabolites involved in plant responses to abiotic and biotic stresses (Ahmed et al, 2021; Wang, Li, et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%